Numerical solution for Duffing-Van Der Pol Oscillator via block method - Rasedee, Ahmad Fadly Nurullah; Abdul Sathar, Mohamad Hassan; Tze, Jin Wong; Lee, Feng Koo; Ramli, Nur Ainna (Union of Researchers of Macedonia, 2021)
The Duffing-Van Der Pol Oscillators is an interesting differential problem with many applications in mechanics and fluid dynamics. Among its most known application involves the chaotic motions in periodic-self excited oscillators and occasionally used to model hydrodynamic forces on canonical structures. The current work aims to provide a numerical solution for the Duffing-Van Der Pol Oscillators in second order differential form using a two-point block method. The two-point block algorithm will be coded in C programming to minimize computational cost (calculation time). Results will show that the proposed method is a practical tool for solving nonlinear differential equation.